Evaluation of metabolic and hormonal parameters in women with PCOS living in Black Sea Region - (:unkn) unknown (My University, 2021)
Polycystic ovary syndrome (PCOS) is the most common endocrinopathy which is frequently associated with metabolic syndrome. The aim of this study is to compare the clinical, biochemical and hormonal characteristics of healthy women and women with PCOS in Black Sea Region. 91 healthy women (Group 1) and 109 PCOS (Group 2) patients were included in this retrospective study. This study was conducted in Samsun Women and Children’s Health Research and Training Hospital between October 2019-May 2020.The anthropometric, clinical and laboratory characteristics of the women were recorded. The Institutional Review Board of the hospital approved the study. IBM SPSS Statistics 22 program was used for statistical analysis. Variables were expressed as mean ± standard deviation or as a number (percentage), and statistical significance was defined as a p value of less than 0.05. In this study, no statistically significant difference was found between patients with PCOS and control subjects in age, height, BMI, waist circumference and waist-to-hip ratio. Weight, BP systolic, BP diastolic and FG scores, were significantly higher in patients with PCOS compared to control subjects. In this study, no statistically significant difference was found between patients with PCOS and control subjects in FSH, estradiol prolactin, TSH, fT3, fT4 and DHEASO4 levels. But, LH, cortisol, total and free testosterone and 17-OH progesteron levels were significantly higher in patients with PCOS compared to control subjects. Also in this study, vitamin B12 and the 25-OH-D levels were significantly lower in patients with PCOS compared to control subjects. HbA1C, fasting blood glucose levels, fasting insulin levels and HOMA-IR were significantly higher in patients with PCOS compared to control subjects . Total-C, LDL-C and TG levels were significantly higher in women with PCOS compared to control subjects. Also, HDL-C levels were significantly lower in women with PCOS compared to control subjects. As a result, the risk of metabolic syndrome is increased in PCOS patients because of high androgen levels, obesity and insulin resistance.